Cloud occurrence frequency and cloud liquid water path for non-precipitating clouds using ground-based measurements over central China. (April 2021) - Xu, Guirong; Zhang, Wengang; Wan, Xia; Wang, Bin
Abstract: Ground-based microwave radiometer (MWR) is with ability to measure liquid water path (LWP) and cloud base height (CBH) with the aid of infrared thermometer (IRT) under all skies. Using the 6-year MWR observations at Wuhan (WH), Xianning (XN) and Jingzhou (JZ) in central China, variations of cloud occurrence frequency (COF) and LWP as well as vertical structure of COF for non-precipitating clouds are investigated. The COFs of middle and high clouds are high in summer and low in winter, and low clouds show very minimum seasonal variations over all three sites. The total COF can reach to 94% in summer and decrease to 37% in winter. Low clouds have high COF in daytime and low COF in nighttime, yet it is opposite for middle clouds. A quasi-bimodal pattern is found in the annual variation of LWP, especially for middle clouds. The diurnal variation of LWP presents partly dependence on CBH. For high clouds, the high LWP in daytime and low LWP in nighttime become significant, showing obvious response to solar radiation. The mean LWPs at WH, XN and JZ are 0.322, 0.469 and 0.243 kg/m 2, respectively, and the high LWP at XN may be related to the dynamic uplift of the nearby hills. Although the vertical structure of COF tends to be unimodal in autumn and bimodal in other seasons, there is a peak of COF always occurring at ~2.5 km. These results benefit the knowledge of cloud properties for non-precipitating clouds over central China. Highlights: Middle and high clouds have high COF in summer and low COF in winter. Diurnal variations of COF for low and middle clouds are opposite. A quasi-bimodal pattern is found in the annual variation of LWP. Diurnal variation of LWP presents partly dependence on CBH. Vertical structure of COF exhibits seasonal difference.